(untitled) (Географический вестник=Geographical bulletin, 2017)
Дается геосистемный анализ состояния и перспектив использования лесопарковой зоны промышленного центра. Исследуется современное состояние ландшафтов ООПТ «Черняевский лесопарк» г.Перми на основе покомпонентной оценки устойчивости и нарушенности природных комплексов локального уровня (типов урочищ) посредством картографического и математического анализа с использованием эмпирических и дистанционных данных. THE LANDSCAPE-ECOLOGICAL APPROACH IN ARRANGEMENT OF GREEN SPACE OF INDUSTRIAL CENTRE In article the landscape-ecological analysis of current state of especially protected natural territory «Chernjaevskyforest park» ofPermwhich results can be taken as a principle recommendations about actions for preservation and optimization of use of territory of green space of industrial centre is presented. In research landscape-geographical methods of research are used: descriptive, comparative, cartographical, the system analysis, space (remote), the GIS-analysis, mathematical. Functional zoning of aforest park, with allocation 5 zones with a various mode of operation which should serve as a starting point on a way on protection and optimization of use of forest parks and increase their sanitary-and-hygienic, aesthetic, and recreational qualities and safety of natural landscapes and ecosystems as a whole became logical result of research.